Hipogonadismo em homens cia vivendo com HIV: prevalência, perfil clínico e metabólico - Felipe Augusto Azevedo Leão (2024)
Male hypogonadism is defined as symptomatic testosterone deficiency. Hypogonadism is common in the population living with HIV, however its prevalence is still controversial, probably due to the lack of standardization in methods for diagnostic definition, among other factors. In addition, its etiology and relationship with endocrine/metabolic conditions in this population remain controversial. This study aimed to investigate the prevalence of hypogonadism in a population of men living with HIV to evaluate the etiology and potential association of hypogonadism with metabolic factors in this cohort. This was a cross-sectional prospective study. Men living with HIV were consecutively recruited from a specialized outpatient clinic in a single tertiary Brazilian center. Hypogonadism was defined by low concentrations of total testosterone (TT) and/or calculated free testosterone (TLc), associated with symptoms suggestive of hypogonadism. Hypogonadism symptoms were assessed using the ADAM questionnaire. When low testosterone was detected, the test was repeated for confirmation, associated with LH measurement to classify hypogonadism as hypo- or hypergonadotropic. In addition, demographic, anthropometric, clinical and metabolic variables were evaluated, as well as variables associated with HIV infection, such as history of opportunistic infections, antiretroviral therapy (ART) used during treatment, and time of infection. Ninety-nine cis men living with HIV were included. Median aged was 38 years (19- 73), and average time of infection was 7 years (1-36). The prevalence of hypogonadism was 33.3%. Of the 23 patients in whom it was possible to classify hypogonadism, 18 (78.3%) had hypogonadotropic hypogonadism, and 5 (21.7%) had hypergonadotropic hypogonadism. The ADAM questionnaire showed a sensitivity of 81.8% and specificity of 50%. The hypogonadal population had a longer time since infection (17 [1-35] vs. 4 [1-36] yrs, p < 0.001), higher prevalence of hypertension (33.3% vs. 3%, p<0.001), , dysglycemia (60% vs. 30%, p=0.001), higher triglyceride levels (154 [50-430] vs. 101 [42- 605]mg/dL, p < 0.001), elevated BMI (> 25) (57.6% vs. 34.9%, p = 0.02) and increased abdominal circumference (30.2% vs 6.1%, p = 0.013) in relation to eugonadal subjects. In this study, one third of men living with HIV had hypogonadism, mostly of central origin (hypogonadotropic). Although it was not possible to determine the etiology, a positive association of hypogonadism with components of the metabolic syndrome, such as abdominal adiposity, hypertension, dysglycemia and triglycerides was observed. The diagnostic evaluation of hypogonadism must be carried out comprehensively, under the risk of underdiagnosis this important condition that affects quality of life significantly and is associated with metabolic factors with an impact on morbidity and mortality.